PERILAKU SEKSUAL MENYIMPANG TOKOH-TOKOH DALAM NOVEL DADAISME KARYA DEWI SARTIKA - Kasman, Revi; Bahardur, Iswadi; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by a number of behaviors found unusual character in the novel by Dewi Sartika Dadaisme. One of them is sexually deviant behavior. To that end, researchers are interested in doing research on sexual behavior deviant figures in the novel by Dewi Sartika Dadaisme. The purpose of this study is to: (1) to describe gender identity disorder figures in the novel by Dewi Sartika Dadaisme, (2) describe the deviation of sexual activity figures in the novel by Dewi Sartika Dadaisme. This type of research is qualitative. In this study, the method used is descriptive method of analysis. The research was conducted over three months, from February till April 2013. Based on the results of this research is that: (1) types of gender identity disorder are found within the homosexual character. This behavior can be seen in figure Jing and Ken, (2) types of deviance sexual activity character in the novel that is incest and adultery. Incest behavior can be seen in figures Magnos and Aleda, and adultery can be seen in figure Tresna, Asril, and Isabella. Deviant sexual behavior that occurs within the high figure is the result of al-ammara passion that makes the id, ego, and super ego in the figures themselves can not function with a balanced stance that led to rejection of the fate that has been revealed by God to them.